Pengetahuan Remaja Tentang Manajemen Kebersihan Menstruasi Berhubungan dengan Sikap Menstrual Hygiene - Wening Ramadhanti; Rohmayanti Rohmayanti; Kartika Wijayanti (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background: The age of menarche has shifted to a younger age, namely 10-13 years, at this age they are easily exposed to information from various sources, for that they need good assistance and education related to menstrual hygiene so that they have good knowledge. It is expected that good knowledge related to menstrual hygiene can form a positive menstrual hygiene attitude, because knowledge is one of the forming good attitudes. This study aims to determine the relationship between knowledge of Menstrual Hygiene (MHM) management and menstrual hygiene attitudes in adolescents aged 10-13 years in Dlimas Village.Methods: This type of non-experimental research is descriptive with a cross sectional approach. The population takes adolescents aged 10-13 years who attend school in the zoning where they live, namely Dlimas Village with a total of 108 populations. Search samples using the slovin formula, obtained 94 samples. The sampling technique used is simple random sampling. The data was processed using the Spearman statistical test.Results: The results of this study most of the respondents have sufficient knowledge about Menstrual Hygiene Management (MKM) as many as 72 respondents (76.6%), and most of the menstrual hygiene attitudes have a positive attitude as many as 57 respondents (60.6%). Spearman statistical test results obtained p value = 0.000 (0.05).Conclusion: There is a relationship between knowledge of Menstrual Hygiene Management (MHM) on menstrual hygiene attitudes in adolescents aged 10-13 years in Dlimas Village.